Reproductive Performance of Pasundan Cattle After Foot-and-Mouth Disease Exposure in South Garut Region, West Java - Setiawati, Euis Nia; Armelia, Vony (Jurnal Veteriner; Vol 25 No 4 (2024), 2025)
Foot-and-mouth disease (FMD) is a highly contagious animal disease that causes significant morbidity and substantial economic losses. The outbreak of FMD occurred in Garut Regency at the end of May 2022, leading to disruptions in production and long-term reproductive performance. This study was aimed to assess the mortality, morbidity, and reproductive performance of Pasundan cattle post-FMD exposure at the farm level. The research was conducted using a survey method with questionnaires containing structured questions directed at farmers. Additionally, in-depth studies were carried out with Fisheries and Livestock Service personnel, as well as direct observations and monitoring. Data collected included: livestock ownership, mortality, morbidity, and reproductive performance indicators such as service per conception (S/C), conception rate (CR), days open, and calving interval. The collected data were analyzed descriptively. The results showed that FMD in Pasundan cattle resulted in a morbidity rate of 86.41%, a mortality rate of 1.83%, and reproductive performance indicators as follows: S/C 1.80 ± 1.5, conception rate 50.0 ± 6.0, days open 140.0 ± 15 days, and calving interval 15.0 ± 1.0 months.